Close, yet different. The Southern European transitions of the 1970s revisited - Diego Palacios Cerezales; Víctor Fernández Soriano (Mélanges de la Casa de Velázquez, 2023)
The idea that Portugal, Greece and Spain shared a model of transition from dictatorship to democracy has been proposed, criticised and revived several times in the past four decades. After a survey of the criteria found in the literature, this article develops a comparative exploration of the three transitions guided by the definition of democracy as an effective system of government built upon the rule of the people, operationalised in three key dimensions. The first one is the reconfiguration of the people by means of the redefinition of the boundaries and contents of the nation. The second is the means deployed to express and channel the political preferences of the population, including elections, referenda and demonstrations. The final dimension is the transformation of the policing apparatus that contributes to make government effective. There were important differences in the direction of change and the centrality of the elements of these three dimensions, especially regarding the choices concering the redefinition of the national community, the use of referenda and the urgency of police reform. However, the three countries successfully became multi-party democracies, suggesting that even if not every path opened ahead for each country would have resulted in democracy, democracy was the possible outcome of many different sets of collective and individual choices.